2022
DOI: 10.1186/s40246-022-00410-2
|View full text |Cite
|
Sign up to set email alerts
|

Maternal obesity alters methylation level of cytosine in CpG island for epigenetic inheritance in fetal umbilical cord blood

Abstract: Background Over the past few decades, global maternal obesity prevalence has rapidly increased. This condition may induce long-lasting pathophysiological effects on either fetal or infant health that could be attributable to unknown unique changes in the umbilical blood composition. Methods A total of 34 overweight/obese and 32 normal-weight pregnant women were recruited. Fifteen umbilical blood samples including 8 overweight/obese subjects and 7 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…In general, low expression of DNMT1, DNMT3a and DNMT3b accelerates gene expression. However, DNMT1 and DNMT3b were signi cantly reduced in obese pregnant women [22]. Compared with GDM, the expression level in obese pregnant women decreased relatively less.…”
Section: Validation Of Gene Expressionsmentioning
confidence: 87%
See 1 more Smart Citation
“…In general, low expression of DNMT1, DNMT3a and DNMT3b accelerates gene expression. However, DNMT1 and DNMT3b were signi cantly reduced in obese pregnant women [22]. Compared with GDM, the expression level in obese pregnant women decreased relatively less.…”
Section: Validation Of Gene Expressionsmentioning
confidence: 87%
“…Umbilical cord blood testing monitors the fetus's health during development in the clinical setting [25]. However, detecting DNA methylation in the cord blood of GDM pregnant women is not ideal [17,22]. To improve this situation, this study reduced the in uence of other characteristics on the results at the sample collection level.…”
Section: Discussionmentioning
confidence: 99%
“…This situation might be due to the distribution of many CpG islands (CGI) with high CpG sequence density in the promoter region. According to statistics, about 70% of vertebrate annotated gene promoters are related to CGI ( 23 , 24 ) and CG sites in CGI are generally in a non-methylated state, while CG sites located outside CGI are more easily modified by methylation, so the methylation level of promoter regions was significantly lower than that of other gene functional elements ( 25 ). When CGI undergo methylation modification, the methylation level of promoter region changes and generally accompanied by the inhibition of gene transcription, resulting in gene silencing ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, gestational weight gain in pregnant women with obesity was associated with cord blood cell DNA methylation [ 109 ]. Average methylated cytosine levels in both the CpG islands and promoters were shown to be significantly decreased in cord blood from overweight and obese groups [ 110 ]. Importantly, a longitudinal birth cohort study, which was across a period from birth to 18 years, showed a significant connection between cord DNA methylation marks and postnatal BMI trajectories [ 111 ].…”
Section: Changed Placenta In Maternal Obesitymentioning
confidence: 99%